Influence of anti-tumour necrosis factor therapy on cardiovascular risk factors in patients with active rheumatoid arthritis. Issue 2 (1st July 2004) - Popa, C; Netea, M G; Radstake, T; Van der Meer, J W M; Stalenhoef, A F H; van Riel, P L C M; Barerra, P
Abstract : Background: Tumour necrosis factor (TNF) is known to increase the concentrations of interleukin (IL) 6 and C reactive protein (CRP) and to induce proatherogenic changes in the lipid profile and may increase the cardiovascular risk of patients with rheumatoid arthritis (RA) and other inflammatory disorders. Objective: To assess whether anti-TNF therapy modifies the cardiovascular risk profile in patients with RA. Methods: The lipoprotein spectrum and the inflammation markers CRP and IL6 were investigated in 33 patients with RA treated with human anti-TNF monoclonal antibodies (D2E7, adalimumab, Humira) and 13 patients with RA given placebo, before and after 2 weeks' treatment. Results: In the anti-TNF treated group, the mean (SD) concentrations of HDL-cholesterol were significantly higher after 2 weeks' treatment (0.86 (0.30) mmol/l v 0.98 (0.33) mmol/l, p<0.01), whereas LDL and triglyceride levels were not significantly changed. Additionally, a significant decrease in CRP (86.1 (54.4) mg/l v 35.4 (35.0) mg/l, p<0.0001), and IL6 (88.3 (60.5) pg/ml v 42.3 (40.7) pg/ml, p<0.001) concentrations was seen in this group. No changes in lipid profile, IL6, or CRP levels were seen in the placebo group. Conclusions: TNF neutralisation with monoclonal anti-TNF antibodies increased HDL-cholesterol levels and decreased CRP and IL6 levels after 2 weeks. Therefore this treatment may improve the cardiovascular risk profile of patients with RA.